Editorial - Fredericks, Bronwyn; Nakata, Martin; Barney, Katelyn (The Australian Journal of Indigenous Education, 2022)
We are very pleased to bring you Volume 51. 1 of The Australian Journal of Indigenous Education. This year the journal shifted to an exciting new open-source platform with Open Journal Systems (OJS) and we are thrilled to be able to bring the AJIE to readers in an even more accessible format. We hope you enjoy this volume of the AJIE. We wish to thank the authors and reviewers for their important contributions to this volume. Many thanks to the Aboriginal and Torres Strait Islander Studies Unit in the Indigenous Engagement Division at The University of Queensland for their financial support of the journal. We are grateful to our Senior Publications Officer Sonia Nitchell for managing the import of the extensive AJIE archive onto the new platform. We look forward to continuing to bring AJIE to readers through our new open access website and ensuring that researchers in Indigenous education globally benefit from increased visibility and engagement with their scholarship. Bronwyn Fredericks, Martin Nakata, and Katelyn Barney